2010
DOI: 10.1074/jbc.m109.041954
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Double-stranded RNA-dependent Protein Kinase (PKR) with the Death Receptor Signaling Pathway in Amyloid β (Aβ)-treated Cells and in APPSLPS1 Knock-in Mice

Abstract: Alzheimer Disease (AD)2 is the leading cause of dementia in the elderly, affecting 25 million people in the world with about 5% of genetic origin. The biological features of AD are neuronal loss, senile plaques predominantly composed of amyloid ␤ peptide (A␤), and the presence of neurofibrillary tangles, leading to a progressive deterioration of cognitive function with loss of memory. Unfortunately, no definitive therapy for AD exists.The involvement of A␤ is clearly established, but mechanisms that underlie n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 50 publications
(71 reference statements)
0
35
0
Order By: Relevance
“…Our previous studies demonstrated that an inhibitor of PKR, the compound C16, prevented the A 42-induced toxicity in human SH-SY5Y neuroblastoma cell line and rat primary neuronal culture, indicating the role of PKR signaling pathway in apoptosis [26][27][28]. Recently, we showed that C16 prevented not only the inflammatory responses in A 42-treated mixed mouse primary co-cultures of neurons, astrocytes and microglia (data submitted) but also in PBMCs of patients with AD [36].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Our previous studies demonstrated that an inhibitor of PKR, the compound C16, prevented the A 42-induced toxicity in human SH-SY5Y neuroblastoma cell line and rat primary neuronal culture, indicating the role of PKR signaling pathway in apoptosis [26][27][28]. Recently, we showed that C16 prevented not only the inflammatory responses in A 42-treated mixed mouse primary co-cultures of neurons, astrocytes and microglia (data submitted) but also in PBMCs of patients with AD [36].…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, many papers described the role of PKR in Alzheimer's disease (AD) from in vitro to in vivo animal studies and in brain of patients with AD. Indeed, it is well-known that PKR negatively controls the translation [22,23], is associated with apoptotic neurons and dystrophic neurites around amyloid deposits [24][25][26], physically interacts with p53 [27] and Fasassociated protein with a death domain (FADD) [28] under amyloid stress. To date, the involvement of PKR in the control of inflammatory response in AD is not elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Caspase-3 activation may be a part of high glucose-induced apoptosis. PKR is reported to mediate apoptosis through multiple mechanisms, including interaction with Fas-associated death domain protein upregulation of the proapoptotic factor Bax and downregulation of Bcl-2 and activation of the caspase-8/caspase-3 pathway [24,25,26,27,28,29,30]. PKR activation abolished the pro-proliferative effects of IGF-I by activating JNK and disrupting the IRS1/PI3K/Akt signaling pathway [6].…”
Section: Discussionmentioning
confidence: 99%
“…Microglial cells may amplify several steps of the amyloid cascade [24,29]. Some studies have shown that this inflammatory response was also present at the periphery with increased levels of circulating cytokines and chemokines in plasma [30,31,32] and in peripheral blood mononuclear cells (PBMCs) [32,33,34] of patients with AD compared to age-matched controls. Furthermore, in patients with AD, both activated T cells and monocytes are present peripherally [35] and infiltrate around amyloid deposits in the brain [36,37].…”
Section: Neuroinflammation In Ad: In Vivo Quantification With Moleculmentioning
confidence: 99%